REVERSE LOGISTIC: A REVIEW PAPER - Wan Hasan, Wan Hasmat; Roni, Mastura; Zaini, Nur Hidayah; Jamil, Muhammad Fairuz (Jurnal 'Ulwan, 2022)
This paper presents a literature review of reverse logistic. The important terminologies and concepts pertaining to reverse logistic are presented. An overview of the importance as well as the urgency to implement reverse logistics is also presented according to the recent studies published in related areas. This paper highlighted the contribution of reverse logistics towards sustainability and how firms could save cost and minimize resources through reverse logistics resulting from reuse of materials, recycling of materials at the end of their product life. The comparison reviewed between reverse and forward logistic have enlighten the need for improvement in supply chain process which requires integrated and effective strategy as to ensure success sustainable product return to the company. Sustainability among manufacturers has become a major concern among various organizational sectors to comply with regulatory requirements and customer pressure. Furthermore, an increased awareness among manufacturers regarding the need to minimize the negative impact of production activities on the environment and need to be more responsible producers to ensure products are safe for the customer’s consumption has led to higher concerns for reverse logistics in Malaysia, as well as the global market.